Psicofonia e desobsessão: uma análise dos discursos dos centros espíritas e das federações - Nascimento, Edileide Bezerra do (2015)
This paper aims at searching about the phenomenon of psychophony in desobsession meetings, emphasizing its practice in spiritual centers and in the FEB (Brazilian Spirit Federation), observing its mechanism and the way its discourse is built, inspired by foucauldian reflections about the discourse analysis of this practice as ruled and the influence of the medium on the psychophony. The interest in analyzing the production of mediumistic discourses in the Centro União Espírita Deus Amor e Caridade, Centro Espírita Caravana da Fraternidade Cristã and Centro Espírita Thomáz de Aquino came from my observations of psychophony activities in desobsession meetings and also the discourse of the Brazilian Spirit Federation BSF on this mediumistic practice. In order to achieve this goal, a qualitative and descriptive research which consisted of two stages was developed: an interview with the President of the Federação Espírita Paraibana (Spirit Federation in Paraiba) and another one with people responsible for mediumistic practices in the centers. The research results show a psychophony practice under FEB‟s control, which forwards it to the FEPB as a discursive field controlled by its mediumistic truths . The centers follow the FEPB rules, even if they disagree with some aspects which are not absorbed in the desobsession meetings.